Tarea de toma de signos vitales básicos con robot humanoide (2021)
This document details the capstone project for Mechanical Engineering. This project consists of designing and manufacturing an attachment prototype that allows the robot Pepper from Softbank Robotics to carry out the the task of performing rounds in a hospital ward collecting the vital signs of patients who are institutionalized in wings of low complexity pathologies for multiple medical and surgical specialties. It has been design to work along a computational prototype developed in the part of this project that corresponds to Compuer Science and Engineering. The end design uses commercial sensors and a 3D-printed cuff that goes around the robot's arm to perform this task. Aditionally it takes a picture of a blood pressure monitor which is stored along the Raspberry Pi and Arduino used to interpret the signals from the sensors. Finally, the data is sent via email by the Raspberry Pi.